Important components of competitive performance in elite male judokas in the heavyweight category - Osipov, A.; Kudryavtsev, M.; Aldiabat, I.; Sweidan, A.; Galimova, A.; Zakharova, L.; Kolokoltsev, M.; Karpenko, E.; Tyupa, P. (Journal of Physical Education and Sport, 2023)
Current competition judo is characterized by a constant activity increase of athletes and a large number of techniques in competition duels. Evaluation of athletes' competition performance should take into account these indicators. Research aim. Analysis and evaluation of important components of the competitive performance of elite male judokas in the heavyweight division and comparison with the components of the competitive performance of elite male judokas in the lightweight division. Materials and methods. Calculation of components of competition performance (CCP) of athletes has been done. Results. The significant (p = 0.05) increase of Nage-Waza technique performance in studied athletes has been revealed. Comparative analysis of data has been conducted with indicators of elite judokas, who competing in lightweight categories. The similar indicators with data of elite lightweight judokas (weighing up to 60 kg and 73 kg) have been revealed in technique of Ne-Waza has been revealed. The similar indicators with elite judokas (weighing up to 66 kg and 83 kg) by the number of Shido in competition duels were identified. Elite super heavyweight judokas gradually intensify the Nage-Waza fight dynamics increasing competition performance. Conclusions. Super heavyweight judokas are advised to reduce the time pauses between attacking maneuvers in competition duels.